Analisis Penyusutan Aktiva Tetap dan Pengaruhnya Terhadap Laba Perusahaan pada PT Aneka Gas Industri - Adila Rahmawaty; Dewi Sri Woelandari Pantjolo Giningroem; Resista Vikaliana; Novita Wahyu Setyawati (Neraca : Jurnal Akuntansi Terapan, 2021)
The study is to know the relationship between a depreciation of the company's fixed activity with its profits, the design of the study USES a quantitative approach with a retroactive correlational research type, the data used is the company's and the Indonesian stock exchange. The sample in this study is the international monetary report on the 2010-2014 period of 2010-2014Research shows that depreciation remains significantly affected profits.Companies or may be defined that the greater value of depreciation of fixed enterprise can affect the profit value of the company